1983
DOI: 10.1111/j.1365-2141.1983.tb02163.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of alpha thalassaemia on the rheology of homozygous sickle cell disease

Abstract: A study of rheological determinants (plasma viscosity, whole-blood viscosity, and erythrocyte deformability) was made in 24 matched pairs of patients with homozygous sickle cell disease, with and without homozygous alpha-thalassaemia 2. Patients with coexisting alpha-thalassaemia showed a significant increase in erythrocyte deformability measured as filtration of washed erythrocytes through 5 micron diameter pores and also as viscosity of whole blood at high shear rate (230s-1) and standard haematocrit (0.45).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
34
0

Year Published

1985
1985
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 16 publications
2
34
0
Order By: Relevance
“…In addition, ␣-thalassemia is also known to cause microcytosis (59), favoring the flow of RBCs through the capillary network. Thus ␣-thalassemia would be expected to dampen the hemorheological and microcirculatory alterations that were postulated above in reference to SCT carriers (20,55,60). In accordance with such hypothesis, RBC deformability and blood apparent viscosity were reported similar in SCT␣-t and C subjects (47).…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…In addition, ␣-thalassemia is also known to cause microcytosis (59), favoring the flow of RBCs through the capillary network. Thus ␣-thalassemia would be expected to dampen the hemorheological and microcirculatory alterations that were postulated above in reference to SCT carriers (20,55,60). In accordance with such hypothesis, RBC deformability and blood apparent viscosity were reported similar in SCT␣-t and C subjects (47).…”
mentioning
confidence: 95%
“…The properties of HbS differ drastically from those of HbA. The main difference lies in the fact that, in its deoxygenated form, HbS polymerizes and induces the sickling process of the RBCs (55). The sickle cell trait (SCT) is characterized by the heterozygous presence of both HbA and HbS (genotype AS).…”
mentioning
confidence: 99%
“…In another study involving patients with HbSC disease, Steinberg and associates 19 found no reduction in vaso-occlusive complications associated with α-thalassemia genotypes. On the other hand, the data provided by Serjeant et al, 4 Higgs et al, 13 Embury et al, 20 and Mears et al 21 support the view that microcytosis and thalassemia lessen the severity of SCD. Our findings are in agreement with this latter view.…”
Section: Discussionmentioning
confidence: 92%
“…Concurrent α-thalassemia may also ameliorate the clinical severity of SCD, principally, it is thought, by improving sickled cell rheology. 4 The unusually high prevalence of α-thalassemia among the Shiite population of eastern Saudi Arabia, [5][6][7] where the mild form of SS occurs, suggests a possible link between α-thalassemia genes and high HbF levels in SCD.…”
mentioning
confidence: 99%
“…[45][46][47][48] Red cells are also more deforma-ble. 49 Clinically, homozygous alpha + thalassemia is associated with persistence of splenomegaly and significantly less chronic leg ulceration and acute chest syndrome. 47 The effect of homozygous alpha + thalassemia on the painful crisis, the frequency of avascular necrosis of the femoral head, other clinical manifestations, and overall survival are unclear.…”
Section: Questions On the Effects Of Alpha Thalassemiamentioning
confidence: 99%